2018
DOI: 10.3390/molecules23081920
|View full text |Cite
|
Sign up to set email alerts
|

Lignan Glycosides and Flavonoid Glycosides from the Aerial Portion of Lespedeza cuneata and Their Biological Evaluations

Abstract: Lespedeza cuneata (Fabaceae), known as Chinese bushclover, has been used in traditional medicines for the treatment of diseases including diabetes, hematuria, and insomnia. As part of a continuing search for bioactive constituents from Korean medicinal plant sources, phytochemical analysis of the aerial portion of L. cuneata led to the isolation of two new lignan glycosides (1,2) along with three known lignan glycosides (3–7) and nine known flavonoid glycosides (8–14). Numerous analysis techniques, including 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Of the 3 recent studies that investigated the anticancer activity of glycosides, one found no significant activity for two glycosides (Shan et al, 2018) and one found moderate anticancer activity for four glycosides (Baek et al, 2018). found relatively strong activity against breast cancer cell lines for cyanidin-3-glucoside isolated from Morus alba (mulberry).…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Of the 3 recent studies that investigated the anticancer activity of glycosides, one found no significant activity for two glycosides (Shan et al, 2018) and one found moderate anticancer activity for four glycosides (Baek et al, 2018). found relatively strong activity against breast cancer cell lines for cyanidin-3-glucoside isolated from Morus alba (mulberry).…”
Section: Anticancer Activitymentioning
confidence: 99%
“…The compounds from the polar fractions were isolated and identified as avicularin and isovitexin ( Fig. 1) [18].…”
Section: Collection Of Plant Materials and Preparation Of Solvent Framentioning
confidence: 99%
“…Phytochemical investigations of LC led to the isolation of tannins, β-sitosterol, pinitol, flavonoids, lignans and their glycosides. The flavonoids include vitexin, myricitrin, rutin, C-glycosyl flavones such as isovitexin, vicenin II, isoorientin, desmodin, lucenin II, and homoadonivernith, and O-glycosyl flavonols such as trifolin, hyperin, avicularin, juglanin, and hirsutrin [4,5].…”
Section: Introductionmentioning
confidence: 99%